An omicron-specific neutralizing antibody test predicts neutralizing activity against XBB 1.5 - Varvel, Stephen; Galdzicka, Marzena; Nystrom, Stephanie; Liu, Hong; Chen, Ge; Ragan, Izabela; Shabahang, Shahrokh (Frontiers in Immunology, 2024)
Understanding the immune status of an individual using neutralizing antibody testing is complicated by the continued evolution of the SARS-CoV-2 virus. Previous work showed that assays developed against the wildtype strain of SARS-CoV-2 were insufficient predictors of neutralization of omicron variants, thus we developed an omicron-specific flow cytometry-based neutralizing antibody test and performed experiments to assess how well it compared to an omicron-specific PRNT assay (gold standard) and whether it could predict neutralizing activity to more recent omicron subvariants such as XBB.1.5. Accuracy of a novel flow cytometry-based neutralizing antibody (FC-NAb) assay was determined by comparison with an omicron-specific PRNT assay. A series of samples were evaluated in both the omicron FC-NAb assay and a second test was designed to assess neutralization of XBB.1.5. Good concordance between the omicron FC-NAb test and the omicron PRNT was demonstrated (AUC = 0.97, p <0.001; sensitivity = 94%, specificity = 100%, PPV = 100%, and NPV = 97%). A strong linear relationship between the omicron FC-NAb and neutralization of XBB1.5 was observed (r = 0.83, p<0.001, figure 2a). Additionally, the omicron FC-NAb test was a very strong predictor of positive XBB1.5 NAb activity (AUC = 0.96, p<0.001; sensitivity = 94%, specificity = 90%, positive predictive value = 90%, and negative predictive values = 94%). Our data suggest that despite continued evolution of the SARS-CoV-2 spike protein, the omicron FC-NAb assay described here is a good predictor of XBB1.5 neutralizing activity, as evidenced by a strong correlation and good predictive performance characteristics.